2011
DOI: 10.1182/blood-2010-05-287649
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 prevents graft-versus-host disease by restraining Th1 differentiation and granulocyte-mediated tissue damage

Abstract: Gene expression profiling of human donor T cells before allogeneic hematopoietic cell transplantation revealed that expression of selected genes correlated with the occurrence of graft-versus-host disease (GVHD) in recipients. The gene with the best GVHD predictive accuracy was SMAD3, a core component of the transforming growth factor-␤ signaling pathway, whose expression levels vary more than a 6-fold range in humans. The putative role of SMAD3 in the establishment of graft-host tolerance remained elusive. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…Consistent with these results, our studies and others have shown that deletion of Smad3-dependent TGF-b signaling in T cells promotes severe graft-versus-host disease (our unpublished data and Ref. 38). In our investigation, Smad3-deficient CD4 + CD25 2 T cells were resistant to TGF-b-induced differentiation into CD4 + CD25 + Tregs in vitro, as expected.…”
Section: Gr1supporting
confidence: 79%
“…Consistent with these results, our studies and others have shown that deletion of Smad3-dependent TGF-b signaling in T cells promotes severe graft-versus-host disease (our unpublished data and Ref. 38). In our investigation, Smad3-deficient CD4 + CD25 2 T cells were resistant to TGF-b-induced differentiation into CD4 + CD25 + Tregs in vitro, as expected.…”
Section: Gr1supporting
confidence: 79%
“…Analysis of cell surface markers and intracellular cytokines was performed by flow cytometry, as described (18). For in vitro-proliferation assays, sorted thymocytes were labeled with 5 mg/ml eFluor 670 for 10 min at 37˚C, washed once with complete medium, and washed three times with PBS.…”
Section: Phenotyping and Proliferation Assaysmentioning
confidence: 99%
“…High IDO expression depletes tryptophan, resulting in apoptosis of alloreactive donor T effectors and generation of iTregs (107,108). Aside from these direct immune regulatory activities, IDO-generated tryptophan by-products may also suppress GVHD directly (89). Clinical studies showed that lower levels of urinary 3-indoxyl sulfate, an indole metabolite influenced by commensal bacteria, correlated with decreased patient survival after allo-HCT (109).…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Transfer of TLR-expressing neutrophils enhanced GVHD mortality compared with the decreased mortality found after the transfer of TLR-deficient neutrophils. The transfer of BM cells lacking SMAD3, a critical signaling component of the TGF-β axis, greatly increased GVHD lethality, which correlated with enhanced Th1 polarization of donor T cells and neutrophil recruitment to the GI tract, mesenteric LNs, and spleen (89). Depleting myeloid cells using anti-Gr-1 mAb therapy greatly improved the outcome of mice receiving SMAD-deficient BM (89).…”
Section: Gvhd and Innate Immunitymentioning
confidence: 99%